Tính:
a) \(\dfrac{-2}{9}+\dfrac{7}{-9};\) b) \(\dfrac{1}{-6}+\dfrac{13}{-15};\) c) \(\dfrac{5}{-6}+\dfrac{-5}{12}+\dfrac{7}{18}.\)
Tính:
a) \(\dfrac{5}{9}:\dfrac{7}{3}\) b) \(\dfrac{2}{7}:\dfrac{8}{5}\) c) \(\dfrac{4}{15}:\dfrac{2}{5}\) d) \(\dfrac{7}{9}:\dfrac{21}{9}\)
a) $\frac{5}{9}:\frac{7}{3} = \frac{5}{9} \times \frac{3}{7} = \frac{{15}}{{63}} = \frac{5}{{21}}$
b) $\frac{2}{7}:\frac{8}{5} = \frac{2}{7} \times \frac{5}{8} = \frac{{10}}{{56}} = \frac{5}{{28}}$
c) $\frac{4}{{15}}:\frac{2}{5} = \frac{4}{{15}} \times \frac{5}{2} = \frac{{20}}{{30}} = \frac{2}{3}$
d) $\frac{7}{9}:\frac{{21}}{9} = \frac{7}{9} \times \frac{9}{{21}} = \frac{{63}}{{189}} = \frac{1}{3}$
Tính:
a) \(\dfrac{5}{6}-\dfrac{4}{6}\) b) \(\dfrac{7}{12}-\dfrac{6}{12}\) c) \(\dfrac{7}{9}-\dfrac{2}{9}\) d) \(\dfrac{16}{5}-\dfrac{9}{5}\)
a: \(\dfrac{5}{6}-\dfrac{4}{6}=\dfrac{5-4}{6}=\dfrac{1}{6}\)
b: \(\dfrac{7}{12}-\dfrac{6}{12}=\dfrac{7-6}{12}=\dfrac{1}{12}\)
c: \(\dfrac{7}{9}-\dfrac{2}{9}=\dfrac{7-2}{9}=\dfrac{5}{9}\)
d: \(\dfrac{16}{5}-\dfrac{9}{5}=\dfrac{16-9}{5}=\dfrac{7}{5}\)
Tính:
a) \(\dfrac{3}{8}+\dfrac{7}{8}\) b) \(\dfrac{7}{9}-\dfrac{4}{9}\) c) \(\dfrac{5}{6}+\dfrac{1}{8}\) d) \(\dfrac{9}{15}-\dfrac{2}{5}\)
e) \(\dfrac{2}{5}+\dfrac{3}{5}+\dfrac{9}{5}\) g) \(\dfrac{8}{10}-\dfrac{1}{10}-\dfrac{3}{10}\) h) \(\dfrac{23}{7}-\dfrac{4}{7}+\dfrac{2}{7}\)
a: \(\dfrac{3}{8}+\dfrac{7}{8}=\dfrac{3+7}{8}=\dfrac{10}{8}=\dfrac{5}{4}\)
b: \(\dfrac{7}{9}-\dfrac{4}{9}=\dfrac{7-4}{9}=\dfrac{3}{9}=\dfrac{1}{3}\)
c: \(\dfrac{5}{6}+\dfrac{1}{8}=\dfrac{20}{24}+\dfrac{3}{24}=\dfrac{20+3}{24}=\dfrac{23}{24}\)
d: \(\dfrac{9}{15}-\dfrac{2}{5}=\dfrac{3}{5}-\dfrac{2}{5}=\dfrac{3-2}{5}=\dfrac{1}{5}\)
e: \(\dfrac{2}{5}+\dfrac{3}{5}+\dfrac{9}{5}=\dfrac{2+3+9}{5}=\dfrac{14}{5}\)
g: \(\dfrac{8}{10}-\dfrac{1}{10}-\dfrac{3}{10}=\dfrac{8-1-3}{10}=\dfrac{4}{10}=\dfrac{2}{5}\)
h: \(\dfrac{23}{7}-\dfrac{4}{7}+\dfrac{2}{7}=\dfrac{23-4+2}{7}=\dfrac{21}{7}=3\)
Tính:
a) \(\dfrac{1}{7}+\dfrac{2}{7}+\dfrac{3}{7}\) b) \(\dfrac{2}{9}+\dfrac{5}{9}+\dfrac{8}{9}\)
c) \(\dfrac{13}{14}-\dfrac{5}{14}-\dfrac{1}{14}\) d) \(\dfrac{7}{11}-\dfrac{4}{11}-\dfrac{3}{11}\)
Tính:
a) \(\dfrac{2}{5}+\dfrac{6}{5}\) b) \(\dfrac{4}{9}+\dfrac{7}{9}\) c) \(\dfrac{6}{7}-\dfrac{4}{7}\) d) \(\dfrac{17}{19}-\dfrac{12}{19}\)
a: \(\dfrac{2}{5}+\dfrac{6}{5}=\dfrac{2+6}{5}=\dfrac{8}{5}\)
b: \(\dfrac{4}{9}+\dfrac{7}{9}=\dfrac{4+7}{9}=\dfrac{11}{9}\)
c: \(\dfrac{6}{7}-\dfrac{4}{7}=\dfrac{6-4}{7}=\dfrac{2}{7}\)
d: \(\dfrac{17}{19}-\dfrac{12}{19}=\dfrac{17-12}{19}=\dfrac{5}{19}\)
Tính:
a) \(\dfrac{7}{3}+\dfrac{4}{9}\) b) \(\dfrac{3}{14}+6\) c) \(\dfrac{7}{8}-\dfrac{1}{2}\) d) \(5-\dfrac{9}{10}\)
a: \(\dfrac{7}{3}+\dfrac{4}{9}=\dfrac{21}{9}+\dfrac{4}{9}=\dfrac{21+4}{9}=\dfrac{25}{9}\)
b: \(\dfrac{3}{14}+6=\dfrac{3+6\cdot14}{14}=\dfrac{84+3}{14}=\dfrac{87}{14}\)
c: \(\dfrac{7}{8}-\dfrac{1}{2}=\dfrac{7}{8}-\dfrac{4}{8}=\dfrac{7-4}{8}=\dfrac{3}{8}\)
d: \(5-\dfrac{9}{10}=\dfrac{50}{10}-\dfrac{9}{10}=\dfrac{50-9}{10}=\dfrac{41}{10}\)
Tính:
a) \(\dfrac{2}{3}+\dfrac{4}{3}\) \(\dfrac{9}{8}-\dfrac{1}{8}\) \(\dfrac{1}{6}+\dfrac{2}{3}\) \(\dfrac{3}{4}-\dfrac{7}{16}\)
b) \(9+\dfrac{2}{7}\) \(\dfrac{3}{8}+10\) \(7-\dfrac{2}{11}\) \(\dfrac{25}{4}-5\)
c) \(\dfrac{2}{3}\times\dfrac{1}{4}\) \(\dfrac{7}{11}\times\dfrac{11}{2}\) \(\dfrac{3}{7}:\dfrac{4}{9}\) \(\dfrac{9}{8}:\dfrac{3}{4}\)
d) \(8\times\dfrac{3}{7}\) \(\dfrac{3}{10}\times6\) \(6:\dfrac{5}{24}\) \(\dfrac{18}{7}:3\)
Giúp em với ạ!!!
Thực hiện các phép tính:
a/ \(\dfrac{2}{3}\)+\(\dfrac{1}{5}\).\(\dfrac{10}{7}\)\(\)
b/ \(\dfrac{7}{12}\)-\(\dfrac{27}{7}\)\(\).\(\dfrac{1}{8}\)
c/ \(\dfrac{5}{9}\).\(\dfrac{7}{13}\)\(\)+\(\dfrac{5}{9}\).\(\dfrac{9}{13}\)-\(\dfrac{3}{13}\).\(\dfrac{5}{9}\)
Em cần ngay ạ!!!
\(\dfrac{2}{3}+\dfrac{1}{5}.\dfrac{10}{7}=\dfrac{2}{3}+\dfrac{10}{35}=\dfrac{70}{105}+\dfrac{30}{105}=\dfrac{100}{105}=\dfrac{50}{21}\)
a) Ta có: \(\dfrac{2}{3}+\dfrac{1}{5}\cdot\dfrac{10}{7}\)
\(=\dfrac{2}{3}+\dfrac{2}{7}\)
\(=\dfrac{14}{21}+\dfrac{6}{21}\)
\(=\dfrac{20}{21}\)
\(\dfrac{7}{12}-\dfrac{27}{7}.\dfrac{1}{8}=\dfrac{7}{12}-\dfrac{27}{56}=\dfrac{392}{672}-\dfrac{324}{672}=\dfrac{68}{672}=\dfrac{17}{168}\)
Tính:
a) \(\dfrac{7}{2}+5\) b) \(9+\dfrac{12}{13}\) c) \(8-\dfrac{9}{11}\) d) \(\dfrac{21}{5}-3\)
a: \(\dfrac{7}{2}+5=\dfrac{7}{2}+\dfrac{10}{2}=\dfrac{17}{2}\)
b: \(9+\dfrac{12}{13}=\dfrac{117}{13}+\dfrac{12}{13}=\dfrac{129}{13}\)
c: \(8-\dfrac{9}{11}=\dfrac{88}{11}-\dfrac{9}{11}=\dfrac{88-9}{11}=\dfrac{79}{11}\)
d: \(\dfrac{21}{5}-3=\dfrac{21}{5}-\dfrac{15}{5}=\dfrac{6}{5}\)